Development of flipbook maker app-based learning resources for high school students - Hadana Ulfannura (Jurnal Inspirasi Pendidikan, 2022)
This study aims to develop learning resources using a flipbook maker application that can facilitate the improvement of student learning outcomes on the material of APBN and APBD for class XI IPS 3 SMAN 1 Tambang. In this development research using 4 stages of the ADDIE model, namely analyze, design, development and implementation. Data collection techniques used interview observations, media and material validation instruments and data on student learning outcomes. The data analysis technique used a validation sheet of media experts and material experts. The results showed that the feasibility value of the learning resource design expert got an average score of 86.45 with a very valid category. Meanwhile, the material expert's feasibility score got an average score of 88.70 with a very valid category. Student responses on the small-scale test showed 67.85 in the very useful category and 32.15 in the useful category. This is also shown from the learning outcomes of students increasing with a significance of = 0.001 less than a significance level of 0.05. Based on the assessment of expert judgment and student learning outcomes after using the flipbook maker application, it can be shown that the flipbook maker that has been developed in general can be declared valid and feasible to use.